(untitled) (LIS TODAY, 2025)
This study investigates the awareness, usage, and satisfaction levels of ICT-based library and information services among users of Vivekanand Central Library, Central University of Jharkhand, Ranchi. Using a structured questionnaire distributed to 125 participants, with a 91.20% response rate, the research explores demographic insights, frequency of library visits, primary purposes for access to library services, and satisfaction levels. The relevant data was analysed using SPSS statistical analysis software. Further, mean, standard deviation and simple percentage were calculated for different variables. Key findings reveal a preference for print resources over electronic formats, with RFID-based automated issue-return being the most utilized ICT service. Challenges like low Internet connectivity and unawareness of available resources were identified, alongside moderate satisfaction levels with ICT based services. Recommendations include improving internet access, expanding ICT training sessions, and enriching the library’s digital collections to serve user needs better. This case study underscores the evolving role of academic libraries in integrating technology to enhance user engagement and accessibility.